ANALISIS EFEKTIVITAS PENDAYAGUNAAN ZAKAT TERHADAP KESEJAHTERAAN RUMAH TANGGA PETANI (Studi Kasus Program M3 Dompet Dhuafa Pada Paguyuban Pertanian Desa Padusan Kabupaten Mojokerto) - AGUNG WICAKSONO (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to determine the effectiveness of utilization of zakat through the program Mustahik Move to Muzakki Karya Masyarakat Mandiri Dompet Dhuafa to the welfare of farm households. This study uses 30 household respondents in the Padusan farming community of Mojokerto regency. The data were collected by using open questionnaire which then analyzed by Paired Sample T-Test and Wilcoxon Test technique by using SPSS24 application and also using CIBEST model to measurepoverty level of material value and spiritual value. The results showed that the effective utilization of zakat to the welfare of farm households because it has a significant influence on income, consumption, and savings from before and after receiving zakat. Based on the CIBEST quadrant seen a prosperous increase of households from the distribution of zakat and also a good spiritual condition in farm households Padusan Village. It is found that the presence of zakat utilization program is able to increase welfare index by 15.66 percent and material poverty index can be reduced by 81.25 percent. Keywords: Zakat, Poverty, Welfare, CIBEST model